Step‐down from non‐invasive ventilation to continuous positive airway pressure: A better phenotyping is required. Issue 4 (28th November 2019) - Patout, Maxime; Dantoing, Edouard; De Marchi, Marielle; Hart, Nicholas; Murphy, Patrick B.; Cuvelier, Antoine
Abstract : See Reply Abstract : See Reply